Зв'язок сейсмічної активності з атмосферним інфразвуком - Сорока, С.О.; Мезенцев, В.П.; Каратаєва, Л.М. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The connection the infrasonic fluctuations in an atmosphere with seismic activity in some region for period 1997–2000 are considered in the work. The model of stationary random process is used for the analysis. The coordination spectral of the characteristics infrasound and seismic activity are shown for the given period of time. The analysis of researches shows change of a spectrum infrasound before earthquake.